Microwave-Assisted Synthesis of Co/CoOx Supported on Earth-Abundant Coal-Derived Carbon for Electrocatalysis of Oxygen Evolution. Issue 8 (1st January 2019) - Pan, Haoran; Wu, Dongling; Huang, Xinning; Xie, Kunpeng; He, Bingcai; Lu, Zhenjie; Liu, Penggao; Cheng, Junxia; Zhao, Xuefei; Masa, Justus; Chen, Xingxing
Abstract : The evident demand for hydrogen as the ultimate energy fuel for posterity calls for the development of low-cost, efficient and stable electrocatalysts for water splitting. Herein, we report the synthesis of Co/CoOx supported on coal-derived N-doped carbon via a simple microwave-assisted method and demonstrate its application as an efficient catalyst for the oxygen evolution reaction (OER). With the optimal amount of cobalt introduced into the N-doped coal-derived, the developed catalyst achieved overpotentials of 0.370 and 0.429 V during water oxidation at current densities of 1 mA cm −2 and 10 mA cm −2, respectively. There was no noticeable loss in the activity of the catalyst during continuous galvanostatic polarization at a current density of 10 mA cm −2 for a test period of 66 h. The synergistic interaction of the Co/CoOx moieties with the pyridinic and pyrollic nitrogen functional groups in the N-doped carbon, as well with the other heteroatoms species in the pristine coal favored enhancement of the OER electrocatalytic performance.